STUDENTS’ PERCEPTIONS OF TIKTOK AS A SPEAKING LEARNING TOOL IN THE ENGLISH DEPARTMENT OF MULAWARMAN UNIVERSITY - Miftahul Jannah; Noor Rachmawaty; Ventje Jany Kalukar (MADINASIKA, 2026)
This study explores the perceptions of students regarding the use of TikTok as a learning tool to enhance English speaking skills. In the digital era, social media platforms like TikTok are increasingly being utilized in educational contexts due to their interactive and accessible nature. This research focuses on students from the English Education Department at Mulawarman University and uses a descriptive qualitative method, involving questionnaires and interviews as data collection instruments. The results indicate that most students have a positive perception of TikTok as a supplementary tool in speaking practice. They believe that the platform helps them become more confident, motivated, and exposed to real-life English usage. Additionally, creating content on TikTok allows students to express themselves creatively and engage more actively with the language. However, some challenges such as distractions and the absence of structured academic feedback were also identified. Overall, TikTok is considered a useful and innovative tool that can support speaking skill development when used effectively in a learning environment.